PENGARUH MODEL PROBLEM BASE LEARNING DENGAN DAKON BILANGAN TERHADAP HASILBELAJAR FPB DAN KPK DI SEKOLAH DASAR - Taufik, Fitri; Masniladevi, Masniladevi; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study is to prove the existence of a positive influence on the Problem Base Learning model with a numbered number on FPB and KPK learning outcomes in grade IV of elementary school. With the quasi-experimental method. This research was conducted at SDS 01 UKS and 07 UKS. Where there were two groups of study samples, namely the control group and the experimental group, each group consisted of 24 and 24 students. The experimental group was taught to use the Problem Base Learning model with number dons while the control group without using the Problem Base Learning and number dacons. Based on data analysis using t-test, obtained t count (4.33) and table (1.67886). So that t count> t table. This proves to be accepted, namely the existence of a positive influence on Problem Base Learning with a numbered number on FPB and KPK learning outcomes in grade IV of elementary school.Keywords: Problem Base Learning, Learning Outcomes, FPB and KPK